Learning Curve in Flexible Cystoscopy among Residents and Urologists in Latin America. - Berrosteguieta, Agustin; Silva, Helen; Vilche, Sofía; Martínez, Levin (Spanish Journal of Medical Education, 2023)
Cystoscopy is essential in urology to diagnose bladder pathologies, especially cancer. Flexible cystoscopy offers certain advantages such as in-office availability. Learning this technique requires varying degrees of endoscopic skill. It is often assumed that procedural competence is achieved in the early years of urological training or within a limited number of procedures. Our objective in the present work was to know the learning curve in this technique among urologists in Latin America. For the study, a survey was conducted among urologists in Latin America, asking if they had received training during their residency and what their learning curve had been like. 83 colleagues participated in the study, including residents, recently graduated urologists and those with more than one year of experience. 70% felt competent to perform cystoscopies without supervision. 57% received training at their residence center. Regarding the learning curve, 86% of respondents reported self-perception of competence among the first 15 cystoscopies. The study included residents, urologists with more than one year of experience, and recent graduates. The availability of flexible cystoscopy during residency was higher for residents (77%) compared to experienced urologists. Most felt competent within 6-10 procedures. In the analysis of residency training, 74% of residents received it. When residents, recently graduated urologists and those with more than one year of experience are analyzed separately, generational differences are observed. Flexible cystoscopy is more common in new generations and training is also more widespread in them. The learning curve is short, with 86% achieving proficiency in 15 procedures.